Self-invertible key on Cipher Polygraphic Polyfunction with eigen matrix based IMIE - Yunos, Faridah; Ayub, Nur Aqilah Fakhira; Mohammad Rasyidi, Nurul Fatin Atiqa; Asbullah, Muhammad Asyraf (Penerbit Universiti Malaysia Perlis, 2024)
Hill Cipher’s System and its modifications are still practiced mainly in sending a secret message involving images. One drawback that the recipient of the message is trying to overcome is to get the decryption key from the cipher text to plain text during the decryption process. Previous studies have proven that using self-invertible keys can reduce the complexity to obtain this key. This paper generates a self-invertible matrix based on Integer-Entry Matrix with all Integer Eigenvalues (IMIE). Subsequently, we executed it into Cipher Polygraphic Polyfunction Cryptosystem and observed the effect. We noticed that when the self-invertible key was employed during even-th transformations, the system became vulnerable to adversary attacks due to recurrence results. It is unnecessary to alter the original message through odd-th transformations, as this process only retrieves the original message.